Strategi Pembelajaran Anak Usia Dini Pasca Pandemi Covid-19 pada Kelompok A di KB-RA Raushan Fikr Tangerang Selatan - Nur Aini Zaida; Choiri Inka Firdani (Fakultas Tarbiyah IIQ Jakarta, 2023)
The purpose of this study was to find out the strategies used by teachers in learning during the Covid-19 pandemic and after. This research uses a qualitative approach with a descriptive research type. This research is located at KB-RA Raushan Fikr, South Tangerang. used in KB-RA Raushan Fikr Group A during the Covid-19 pandemic is a direct learning strategy with two learning systems, namely online learning using the zoom meeting application and WhatsApp and also offline private class learning. The material made in learning at KB-RA Raushan Fikr group A is adjusted to the Standards for the Level of Achievement of Child Development (STTPA). The learning methods used at KB-RA Raushan Fikr during the Covid-19 pandemic were demonstration methods, storytelling methods, playing methods, and also lecture methods. learning media in the form of online such as using HP/laptop electronic media by using several learning support applications such as Zoom Meeting and WhatsApp and offline media such as using media in the surrounding environment, worksheets, and so on. The evaluation technique carried out at KB-RA Raushan Fikr group A used observation with daily notes, performance, work results, conversations, assignments, portfolios, and also anecdotal notes.